(untitled) (Semiárida, 2020)
The aim or this study was to investigate the presence of larvae of cutworms, identify the species in which they belonged, and establish which was their active period in pastures or alfalfa (Medicago sativa L.) in two different subregions of the Eastem physiographic area of La Pampa Province in Argentina. Samplings were carried out during years 2001 and 2002 in the districts of Maraco, Trenel, and Capital. Two plots of alfalfa were revised each year. Five stations were delimited in each plot and 20 to 40 plants were sheeted in each station and in them the crown, the adjacent litter and the first five centimetres depth of soil were revised. Larvae of cutworms were collected manually and identified in the lab. They were keep in a breeding box, with artificial diet until adult emergence. Results suggest that five cutworms complex includes four species of Noctuidae, I.e., Agrotis gypaetina Guen6e, Agrotis maiefida Guenee, Peridroma saucia (Huber) and Euxoa bilitura Guenee. The two last species were sporadicly recorded and in low density whereas the two first species were most abundant, detected from July-August, when they had reached 2 mm long and by the end of October they measured 40- 45 mm long. The active period of the larva - i.e., they feed and thus can damage crops - was August to November.